Attributes of Successful Educational Change in the Background of Reform Efforts - Vančíková, Katarína; Porubský, Štefan; Basarabová, Barbara; Šukolová, Denisa (Pedagogika, 2023)
The aim of the study is to investigate what ideas those involved in the implementation of educational change (teachers, school management, and pedagogical leaders) in Slovakia have about successful curriculum reform, what attributes they assign to it, and what characteristics dominate their ideas. Using the quantitative-qualitative Q-methodology design, five different opinion clusters have been identified, each of which can be interpreted against the background of the post-2008 Slovak experience of failed attempts at educational reform.